Textbook of Aramaic ostraca from Idumea volume 1, Dossiers 1-10: 401 commodity chits - Porten, Bezalel 1931-; Yardeni, Ada; Kletzing, Matt; Han, Eugen (Winona Lake, Indiana Eisenbrauns, 2014)
Frontmatter -- Contents -- Tables -- Figures -- Comparative List of Entries -- Supplementary Material on CD -- Abbreviations and Select Bibliography -- Introduction -- Explanation of Typographic Conventions -- Grain Equivalencies -- Terminology of Ceramic Descriptions -- Terminology of Palaeographic Descriptions -- Numeration Legend -- Texts -- A1–10 Commodity Chits -- A7–10 Dossiers of Prominent Individuals
Some 340 Aramaic ostraca of the Persian and Hellenistic periods have been excavated at 32 sites in Israel, from Yokneam in the north to Eilat in the south, with Arad and Beersheba being the main contributory sites. By far, however, the largest cache of texts is what has come to be known as “the Idumean ostraca”. These did not come from formal excavations but began to appear on the antiquities market in 1991. Since then, some 2,000 ostraca have reached 9 museums and libraries and 21 private collections. Of these, the majority are still not formally published, and in this volume (and those to follow), Bezalel Porten undertakes to provide a comprehensive edition of all these texts, in many cases as an editio princeps. Porten, with the expert epigraphic assistance of Ada Yardeni and hand-copies by her as well, here provides the first volume of texts, organized by “dossier” based on the primary personage cited in the text. Color photographs (where available), ceramic descriptions, hand-copies, transcription, translation, and commentary are provided for each text, along with figures and tables, and introductions and summaries of each dossier. An included CD contains a catalogue of all the texts and three color key-word-in-context concordances, for words, personal names, and months for the entire corpus. This publication will become the primary resource for information on these texts
Mode of access: Internet via World Wide Web.
In English
Keywords: Aramaic language -- Texts; Ostraka -- Edom (Kingdom); HISTORY / Ancient / General; Idumean ostraca; commodity chits; payment orders; Accounts; workers' texts; name lists; jar inscriptions; Letters; land descriptions; no text ostraca; Persian Empire; Idumea; Aramaic; Makkedah